Comparison of Children’s Double Dichotic Digits and SCAN-3 Competing Words Free Recall Scores - Kelley, Kairn Stetler; Littenberg, Benjamin (Journal of the American Academy of Audiology, 2019)
Practice guidelines do not specify which test recordings are best for assessing dichotic deficit or interaural asymmetry. Dichotic Digits and SCAN-3 Competing Words Free Recall are among the most widely used dichotic tests, but it is not known if the choice of test results in important differences in the identification of children with deficits or if they can be used interchangeably.To determine whether two commonly used dichotic tests, SCAN-3 Competing Words Free Recall (CW) and Musiek’s Dichotic Digits (DD), agree on interaural asymmetry and dichotic deficit in children.CW and DD tests were administered to all participants. Each participant had a single study visit.Sixty volunteers aged 7–14 years with normal hearing sensitivity participated in the study.Hearing sensitivity, CW, and DD performance were measured at a single study visit. We used Spearman’s rho (ρ) to assess associations between rank ordering of participants by each test and the kappa statistic (κ) to assess decision consistency between tests.Participants were rank-ordered similarly by CW and DD for the right ear (ρ = 0.58), left ear (ρ = 0.51), and total (ρ = 0.73) scores, but not for interaural asymmetry (ρ =0.18). They agreed no better than chance on direction of ear advantage (κ = 0.01, p = 0.93) and had poor agreement on which children scored below cut-scores (κ = 0.22, p < 0.01). DD identified significantly more participants with deficits (n = 18) than CW (n = 3) (p < 0.001).Although children with high scores on one test tend to have high scores on the other, CW and DD do not agree on ear advantage or the presence of deficit. They are not interchangeable for clinical use. Additional research is needed to determine whether either is appropriate for identifying children who would benefit from treatment for dichotic listening deficits.
Keywords: agreement; decision consistency; dichotic listening tests; technology assessment